Analysis of N and P-Type Semiconductor Materials in Electricity - Adelia Azzahra; Audia Early Setiawan; Bintang Dwi Cahya; Vito Pranando; Solly Aryza, (International Journal of Economic, Technology and Social Sciences (Injects), 2023)
In everyday life, there are several types of electrical materials, including conductors, insulators and semiconductors. Apart from materials that can conduct and withstand electric current, semi-conductor materials are also needed, namely electrically conducting materials that are between electrical conductors and electrical insulators. This material functions as an insulator at low temperatures, and is a conductor at quite high temperatures, but cannot conduct heat like conductor materials. This type of semi-conductor material is also not very dangerous, but you also need to be careful when using it. The most frequently used semi-conductor materials are carbon, silicon and germanium.